Poorly differentiated small cell carcinoma of the pancreas: a case report and review of the literature - Berkel, Simone; Hummel, Frank; Gaa, Jochen; Back, Walter; Hofheinz, Ralf-Dieter; Queißer, Wolfgang; Singer, Manfred V.; Löhr, J.-Matthias (Pancreatology, 2004)
Small cell carcinoma (SCC) of the pancreas is a rare malignancy with an extremely poor prognosis. We present the case of a 74-year-old man with a 2-month history of upper abdominal discomfort who was diagnosed with SCC of the pancreas tail, involvement of peri-pancreatic and mesenteric lymph nodes and multiple liver metastases (extended disease). A CT scan and a positive somatostatin receptor scintigraphy showed no evidence of a primary lung tumour. The diagnosis of a SCC was confirmed by biopsy. Local tumour control could be achieved by gemcitabine once a week and a long-acting somatostatin analogue once a month, but liver metastasis showed progress. Thus, 5-fluorouracil on a weekly basis was started. The patient died 8 months after diagnosis and had not been hospitalised in the meantime.
Gesehen am 03.05.2022